PENGEMBANGAN KURIKULUM PAI DI UNIVERSITAS NEGERI YOGYAKARTA - Nia Karnia; Nur Aini Farida; Ferianto Ferianto (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The PAI curriculum at UNY was formed to plan, manage and evaluate PAI learning activities in accordance with the educational objectives that have been set. PAI is a family of personality development courses ( MPK) in the structure of general courses (MKU) that must pass and have a weight of 3 credits, with a course code of UNU 201. Judging from its position, it is a course that equips students in the form of basic abilities about understanding, passion and experience of basic human values, as creatures of God, as individuals, family members, communities, citizens and as part of nature. In addition to PAI lectures, UNY implements the PAI tutorial program which is a special activity that emphasizes deepening and mastering the practical skills of worship and literacy of the Qur'an which is required of students who take Islamic Religious Education courses. In general the approach applied is the approach of academic subjects. Evaluation of PAI learning is carried out in two ways, namely tests and observations carried out by lecturers who teach courses to students.Keywords: Curriculum development, PAI, UNY